ANALYSIS OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN LEARNING ISLAMIC RELIGIOUS EDUCATION IN STATE JUNIOR HIGH SCHOOLS IN SERANG CITY, BANTEN, INDONESIA - Pratiwi, Herlina; Nupus, Dian; Heri, Heri (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
This research aims to determine the implementation of the free learning curriculum in Serang City Middle Schools and to analyze the preparation of teaching modules in the free learning curriculum used in Serang City Middle Schools. This research method uses a qualitative research approach. The sampling technique uses purposive sampling with the criteria of schools that have implemented an independent curriculum. There were 5 junior high schools that were used as samples because they had implemented the independent learning curriculum, namely SMP Negeri 3 Serang City, SMP Negeri 4 Kota Serang, SMP Negeri 9 Kota Serang, SMP Negeri 13 Kota Serang, and SMP Negeri 14 Kota Serang. Implementation will be carried out in class VII starting in the odd semester of the 2022–2023 academic year. The research results show that teachers have implemented an independent curriculum. The learning tools used in the independent learning curriculum are in the form of teaching modules, which are detailed in the form of lesson plans. PAI subjects are divided into several materials, namely Fiqh, Aqidah Akhlak, Al-Qur'an Hadits, and SKI. The application of the independent learning curriculum teaching modules, apart from being in the form of learning materials, is also in the form of projects, which must be carried out at least three projects in one year. One project is given 120 hours, and the implementation is handed over to the school. Teachers implement the independent curriculum with enthusiasm and strive to continue learning to implement the independent curriculum in accordance with applicable regulations.